Syphoning confidence : piracy and fuel theft in Southeast Asia - Euan, Graham (2015)
A spate of fuel-syphoning attacks on small tankers in the Straits of Malacca of South China Sea is helping to perpetuate a misleading narrative of resurgent piracy in Southeast Asia. However, they reveal transnational dimensions to maritime crime that require a concerted stakeholder response.